Blockchain-based ICOs: Pure hype or the dawn of a new era of startup financing? - Lennart Ante; Philipp Sandner; Ingo Fiedler (Journal of Risk and Financial Management, 2018)
This study explores the determinants of initial coin offering (ICO) success, where success is defined as the amount of capital a project could raise. ICOs are a tool for startups in the blockchain ecosystem to raise early capital with relative ease. The market for ICOs has grown at a rapid pace since its start in 2013. We analyze a unique dataset of 278 projects that finished their ICOs by August 2017 to assess determinants of funding success that we derive from the crowdfunding and venture capital literature. Our results show that ICOs exhibit similarities to classical crowdfunding and venture capital markets. Specifically, we identify resemblances in determinants of funding success regarding human capital characteristics, business model quality, project elaboration, and social media activity.
Keywords: 330; initial coin offering; blockchain; venture capital; crowdfunding